The Role of Sharia in the Regulation of Halal Issues in the Contemporary World - Sholihah, Ananda Mar Atush (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: The rule of Sharia in regulating halal issues in the contemporary world is a complex and multifaceted one. Islamic scholars and jurists have debated the issue for centuries, and there is no one definitive answer. However, there are a number of key principles that can be drawn from the Quran and Sunnah that provide guidance on how to approach the issue of halal in the modern world. This study explores the role of Sharia in regulating halal issues in the contemporary world. The aim of this research is to analyze the recent developments and challenges in the field of halal regulation from an Islamic perspective. Methodology: A qualitative research approach is employed, using a literature review and analysis of relevant secondary sources. Results: The findings indicate that Sharia plays a crucial role in guiding the regulation and certification of halal products and services. Value: It provides a comprehensive framework that encompasses not only the technical aspects of halal, but also ethical and sustainable considerations. Sharia-based halal standards and regulations ensure the traceability, authenticity, and integrity of halal products, thereby safeguarding the interests of Muslim consumers. Furthermore, the research reveals the challenges faced in implementing Sharia-based halal regulation, such as the lack of uniform standards and the need for international harmonization. However, these challenges also present opportunities for collaboration and innovation in the halal industry. This study contributes to the existing body of knowledge by highlighting the importance of Sharia in addressing contemporary halal issues and providing insights for policymakers, industry practitioners, and scholars in the field.